The Under-age Marriage during the Pandemic: The Best Interest of the Child Principle - Hilmi, Ahmad Faris; Kiram, Muhammad Zawil (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
This article focuses on juvenile marriages that took place during the Covid-19 pandemic. In addition, the causes of child marriage, its negative consequences, and the preservation of children in the family and marriage is seen as an application of the principle in placing the child’s best interests first? This research is descriptive-analytic in nature, describing the facts about child marriage that occurred in the pandemic era and analyzing why this phenomenon occurs. Several factors, including education, a lack of understanding of reproductive health in adolescents that leads to risky sexual behavior among children, economic factors (poverty), cultural factors (traditions/customs), and matchmaking, were found to influence child marriage in this study.